Ambient precipitation determines the sensitivity of soil respiration to precipitation treatments in a marsh. Issue 8 (7th February 2023) - Li, Xinge; Hou, Yalin; Chu, Xiaojing; Zhao, Mingliang; Wei, Siyu; Song, Weimin; Li, Peiguang; Wang, Xiaojie; Han, Guangxuan
Abstract: The effects in field manipulation experiments are strongly influenced by amplified interannual variation in ambient climate as the experimental duration increases. Soil respiration (SR), as an important part of the carbon cycle in terrestrial ecosystems, is sensitive to climate changes such as temperature and precipitation changes. A growing body of evidence has indicated that ambient climate affects the temperature sensitivity of SR, which benchmarks the strength of terrestrial soil carbon–climate feedbacks. However, whether SR sensitivity to precipitation changes is influenced by ambient climate is still not clear. In addition, the mechanism driving the above phenomenon is still poorly understood. Here, a long‐term field manipulation experiment with five precipitation treatments (−60%, −40%, +0%, +40%, and +60% of annual precipitation) was conducted in a marsh in the Yellow River Delta, China, which is sensitive to soil drying–wetting cycle caused by precipitation changes. Results showed that SR increased exponentially along the experimental precipitation gradient each year and the sensitivity of SR (standardized by per 100 mm change in precipitation under precipitation treatments) exhibited significant interannual variation from 2016 to 2021. In addition, temperature, net radiation, and ambient precipitation all exhibited dramatic interannual variability; however, only ambient precipitation had a significant negative correlation with SR sensitivity. Moreover, the sensitivity of SR was significantly positively related to the sensitivity of belowground biomass (BGB) across 6 years. Structural equation modeling and regression analysis also showed that precipitation treatments significantly affected SR and its autotrophic and heterotrophic components by altering BGB. Our study demonstrated that ambient precipitation determines the sensitivity of SR to precipitation treatments in marshes. The findings underscore the importance of ambient climate in regulating ecosystem responses in long‐term field manipulation experiments. Abstract : Ambient precipitation had a significant negative correlation with the sensitivity of SR to field precipitation treatments in marshes. Based on the increase in the interannual variability of ambient precipitation over the past 61 years (1961–2021), amplified interannual variation in ambient precipitation in the future may modulate the sensitivity of SR to climate changes. DPPT, decreased precipitation; IPPT, increased precipitation; PV, precipitation variability; SR, soil respiration.